Keabsahan Laporan Tindak Pidana Kekerasan dalam Rumah Tangga Pasca Perceraian - Wijaya, jesica Natalia; Prasetyo, Boedi (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2025)
This study aims to analyze the validity of reports on domestic violence (DV) crimes filed after divorce, focusing on the Military Court Decision Number 85-K/PM.II-08/AD/II/2022. This article is categorized as normative legal research using a statutory approach and a case approach. The methodology employed is descriptive analytical study. The study concludes that reports of domestic violence crimes filed after divorce remain legally valid, provided they meet the formal and material requirements as stipulated by applicable regulations. The military court's decision in this case highlights the importance of recognizing victims' rights to justice, regardless of marital status.